Psychosocial Implications and Quality of Life in Patients with Hidradenitis Suppurativa Compared to Those With Atopic Dermatitis and Psoriasis: a Cross-sectional Case-control Study - Alya AlSiyoufi; Saleh Almohaimeed; Sawsan Alsiyoufi; Louai Salah (Mattioli1885, 2023)
Introduction: Hidradenitis suppurativa (HS) is a chronic inflammatory skin disease that has been reported to have the greatest negative impact on quality of life (QoL) and psychosocial factors when compared with other skin conditions.Objectives:  To assess psychosocial impact and QoL impairment in patients with HS.Methods: This cross-sectional case-control study included a case group with HS and a control group with psoriasis or atopic dermatitis diagnosed by a dermatologist at a public hospital in Jeddah, Saudi Arabia from 2016 to 2019. Data were obtained from medical records at a ratio of 1:2. Patients were contacted via telephone and asked to complete Arabic-validated questionnaires (Dermatology Life Quality Index [DLQI], Rosenberg Self-Esteem Scale, and Hospital Anxiety and Depression Scale) and a survey containing pictures to identify Hurley stage.Results: The study included 46 patients and 101 controls (eczema, 50; psoriasis, 51). Patients had significantly higher DLQI and depression scores than did controls (P < 0.05). Anxiety and depression scores were significantly higher in women than men (P < 0.05). Cases with Hurley stage 3 had significantly higher DLQI scores than those with Hurley stages 1 and 2. Controls had a significantly higher percentage of employed participants (P < 0.05).Conclusions: HS had a greater psychosocial impact on QoL than psoriasis or atopic dermatitis and was associated with a lower employment rate. Women were more affected by the disease than men. Therefore, we recommend paying close attention to the psychosocial aspects of the disease and establishing educational programs and support groups for patients with HS.